Clinical features of hereditary angioedema and warning signs (H4AE) for its identification - Giavina-Bianch, Pedro F.; Aun, Marcelo Vivolo; Garcia, Juliana Fóes Bianchini; Gomes, Laís Souza; Ribeiro, Ana Júlia; Takejima, Priscila; Agondi, Rosana Câmara; Kalil, Jorge; Motta, Antonio Abilio (Clinics, 2022)
Objectives: The study describes a case series of hereditary angioedema with C1 Inhibitor Deficiency (C1INH-HAE) in order to corroborate six clinical warning signs “HAAAAE (H4AE)” to enable early identification of this disease. Methods: The authors analyzed the C1INH-HAE cohort to analyze the clinical aspects of the present study's patients and corroborate the six clinical warning signs of the Hereditary Angioedema Brazilian Guidelines. Data regarding demographics, the onset of disease, time to diagnosis, frequency of attacks per year, organs involved, triggers, crisis duration and their outcomes, and disease treatment were collected. Then the authors developed an acronym, H4AE, to help healthcare professionals remember the warning signs. Results: The authors included 98 patients in the study, with a mean age of 38.1 years, 67.3% being female, and 75.3% with a family history of HAE. HAE diagnosis was delayed, on average, 13.7 years after its initial manifestation. Exploratory laparotomy was reported by 26.9%, and orotracheal intubation by 21.3% of the present study's patients; 61.3% and 30.3% of them were admitted at least once in the hospital and in the intensive care unit, respectively. The authors constructed an acronym “H4AE” with the six warning signs of HAE: Hereditary, recurrent Angioedema, Abdominal pain, Absence of urticaria, Absence of response to antihistamines, Estrogen association. Conclusion: C1INH-HAE is still underdiagnosed and associated with high morbidity. The study showed clinical features of this disease, corroborating the warning signs, which may be useful in raising awareness and improving the diagnosis of C1INH-HAE. The authors suggest the acronym “H4AE” to remind the warning signs.